Extension rates across the northern Shanxi Grabens, China, from Quaternary geology, seismicity and geodesy - Middleton, T; Elliott, J; Rhodes, E; Sherlock, S; Walker, R; Wang, W; Yu, J; Zhou, Y (Oxford University Press, 2017)
Discrepancies between geological, seismic and geodetic rates of strain can indicate that rates of crustal deformation, and hence seismic hazard, are varying through time. Previous studies in the northern Shanxi Grabens, at the northeastern corner of the Ordos Plateau in northern China, have found extension rates of anywhere between 0 and 6 mm/a at an azimuth of between 95 and 180 °. In this paper we determine extension rates across the northern Shanxi Grabens from: offset geomorphological features and a variety of Quaternary dating techniques (including new IRSL and Ar-Ar ages); a Kostrov summation using a 700 year catalogue of historical earthquakes; and recent campaign GPS measurements. We observe good agreement between Quaternary, seismic and geodetic rates of strain, and we find that the northern Shanxi Grabens are extending at around 1 to 2 mm/a at an azimuth of ≈ 151 °. The azimuth of extension is particularly well constrained and can be reliably inferred from catalogues of small earthquakes. We do not find evidence for any substantial variations in extension rate through time, though there is a notable seismic moment rate deficit since 1750. This deficit could indicate complex fault interactions across large regions, aseismic accommodation of deformation, or that we are quite late in the earthquake cycle with the potential for larger earthquakes in the relatively near future.